Speech Delay sebagai Manifestasi Disregulasi Emosi dan Ketidaksiapan Neuropsikologis pada Anak Usia Dini - Tri Gunadi; Andik Matulessy; Basilia S. W (Pusat Riset dan Inovasi Nasional, 2025)
Speech delay in early childhood is often conceptualized as a purely linguistic deficit. This perspective tends to emphasize articulation training and vocabulary expansion while overlooking the child’s neuropsychological readiness for verbal communication. Recent empirical evidence suggests that expressive language development is closely related to emotional regulation, attentional capacity, and executive functioning, which collectively shape a child’s readiness to engage in communication. This article aims to examine speech delay as a manifestation of emotional dysregulation and insufficient neuropsychological readiness, and to discuss its implications for early childhood intervention. A narrative review of empirical studies published within the last five years was conducted to synthesize findings on the relationship between language development, emotional regulation, and executive functions. The review indicates that interventions that neglect emotional readiness may increase stress and hinder functional language development. This article highlights the importance of a neuropsychological framework that prioritizes emotional regulation and self-regulatory capacity as foundational components in addressing speech delay in young children.